2012
DOI: 10.1130/g33059.1
|View full text |Cite
|
Sign up to set email alerts
|

Tristan da Cunha: Constraining eruptive behavior using the 40Ar/39Ar dating technique

Abstract: The historically active volcanic ocean island of Tristan da Cunha exhibits a complex and dynamic history, with numerous, often compositionally distinct, parasitic centers punctuating the large edifice. To date, the temporal relationship between differing styles of activity has been unclear. We have applied high-precision 40Ar/39Ar dating to 15 carefully selected samples from Tristan da Cunha to ascertain spatio-temporal relationships of recent volcanism, explore episodicity, and establish if the most recent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…88 Pigbite to the west of Big Point (Fig. 1), where well-stratified basanitic and tephritic flows are exposed 98 (Hicks et al, 2012). There were no folding or faulting tectonic features in the sampling area, with the only 99 alteration to the strata being igneous intrusions.…”
mentioning
confidence: 99%
“…88 Pigbite to the west of Big Point (Fig. 1), where well-stratified basanitic and tephritic flows are exposed 98 (Hicks et al, 2012). There were no folding or faulting tectonic features in the sampling area, with the only 99 alteration to the strata being igneous intrusions.…”
mentioning
confidence: 99%
“…During phase one, volcanological data gathering involved field mapping, geological sampling and analysis via 40 Ar/ 39 Ar geochronology, refining views about timing, style, location and likely patterns of activity (Hicks et al, 2012). Scientific uncertainty was quantified using an established structured elicitation technique 6 (Cooke and Goosens, 1999), using volcanological data collected in phase one.…”
Section: Methodsmentioning
confidence: 99%
“…Given that the summit slopes are very steep, and the channelising nature of the gulches, the consequences of a summit eruption for the Settlement are different than an eruption on lower-lying areas. Although the two most recent eruptions occurred on low-lying coastal strips (1961)(1962) dome and flows; Stony Hill dome and flows (∼ 200-300 years BP)), the new temporal framework revealed that future eruption on the flanks, or from the summit, cannot be discounted (Hicks et al, 2012).…”
Section: Physiography Of Tristan and Timing Of Volcanic Eventsmentioning
confidence: 99%
See 2 more Smart Citations